Work Capacity and Longer Working Lives in Belgium - Alain Jousten; Mathieu Lefèbvre (Institute for the Study of Labor (IZA), 2015)
We explore the link between health indicators and employment rates of the population aged 55 or more. Our focus lies on work capacity as a key determinant of employment. Using cohort mortality information as a proxy for overall health outcomes, we establish a substantial untapped work capacity in the population 55+. Similar results are obtained when relying on individual-level objective and subjective health and socioeconomic parameters as predictors.
Keywords: J14; J21; J26; 330; employment; retirement; work capacity